From responsibilities to responsibility: a study of the effects of translation workflow automation - Herbert, Sarah; do Carmo, Félix; Gough, Joanna; Carnegie-Brown, Anu (The Journal of Specialised Translation, 2023)
This article studies the effects of automating a job allocation system, in a translation company of approximately 130 employees. Perceptions of the effects of automation on roles and responsibilities were collected through a short survey, answered by 38 project managers and translators. This evolved to an analysis of effects on the deeper notion of professional responsibility, related to accountability, control, engagement and understanding of a translation workflow. The results first reflect on positive and negative effects of automation, notably indicating that automation can both restrict and enhance professional roles and autonomy. The focus then turns to perceptions of workers’ main responsibilities, when impacted by a new automated process. One key result suggests increased difficulty in prioritising these duties. Furthermore, translators prefer not being restricted by their specialisations and favour the development of new skills. Another relevant finding of the study shows in-house translators as being the group who alludes more frequently to concepts related to responsibility. The article contributes to the study of socio-technical changes in the translation industry, suggesting that responsibility plays an important part in highlighting the effects of technology, not only on professional and organisational practices, but also on individual perceptions of accountability and job satisfaction.